Assessment of Geography Teaching-Learning Process Through Game, in Pre-University Education - Toma, Florentina; Diaconu, Daniel Constantin; Dascălu, Gabriel Vasile; Nedelea, Alexandru; Peptenatu, Daniel; Pintilii, Radu-Daniel; Marian, Marin (Studia Universitatis Babeș-Bolyai. Geographia., 2022)
"Assessment of Geography Teaching-Learning Process Through Game, in Pre-University Education. A general problem recognized in the educational process is the need to identify the manner in which the teacher, as the factor with the greatest influence on learning, increases the students' school performance. The creation of a tool in the form of an interactive website, using types of languages to improve an easy understanding of learning, the formation of specific competences and the students’ enhanced motivation for study are the objectives of this study. This study evaluates the teaching-learning system through its own created game, using certain types of computer languages: HTML, CSS and JavaScript, from the perspective of measuring the impact of the effect on tests in the formative assessment sequence of students, compared to other teaching-learning methods. The experiment, observations, performance analysis and qualitative Google Forms questionnaires, suggested a high degree of student engagement and how game technology can facilitate teaching. As the results have shown that there is a strong difference between experimental and control groups, it indicates that educational play has had a positive impact on learning and increasing students' interest, confirming the advantages of learning through play. The teaching-learning model can be extended to use at national and international level. Keywords: teaching-learning through game; Geography; Google Forms; HTML computer language; CSS and JavaScript. "